Empires of the senses bodily encounters in Imperial India and the Philippines - Rotter, Andrew Jon (Oxford University Press, 2019)
"This groundbreaking work offers a sensory history of the British in India from the formal imposition of their rule to its end (1857-1947) and the Americans in the Philippines from annexation to independence (1898-1946). A social and cultural history of empire, it analyzes how the senses created mutual impressions of the agents of imperialism and their subjects, and highlights connections between apparently disparate items, including the lived experience of empire, the comments (and complaints) found in memoirs and reports, the appearance of lepers, the sound of bells, the odor of excrement, the feel of cloth against skin, the first taste of meat spiced with cumin or of a mango. Men and women in imperial India and the Philippines had different ideas from the start about what looked, sounded, smelled, felt, and tasted good or bad. Both the British and the Americans saw themselves as the civilizers of what they judged backward societies and believed that a vital part of the civilizing process was to put the senses in the right order of priority and to ensure them against offense or affront. People without manners that respected the senses lacked self-control; they were uncivilized and thus unfit for self-government. Societies that looked shabby, were noisy and smelly, felt wrong, and consumed unwholesome food in unmannerly ways were not prepared to form independent polities and stand on their own. It was the duty of allegedly more sensorily advanced westerners to put the senses right before withdrawing the most obvious manifestations of their power. This study of Indians and Filipinos' ideas of what constituted sensory civilization and the imperial encounter with British and American sense-orders shows the compromises between these nations' sensory regimes"--